Friday
March 24, 2017

Post a New Question

Posted by on Wednesday, November 5, 2008 at 2:38am.

i don't understand how to do these
1+3x-x=x-4+2z
3+3x-(x-2)=3x+4

  • algerbra 1 - , Wednesday, November 5, 2008 at 2:50am

    Combine similar terms (constants; terms that end in x; etc).

    In the first case, you end up with
    1 + 2x = x - 4 + 2z
    which can be rewritten
    5 + x = 2z

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question